(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Initially, during the investigation, 4 rabbits were taken for the experiment and they were divided into 4 experimental groups. First, they are checked by weight, then we check them by palpation. The age of rabbits is determined, so we study the physiology of rabbits.